Comparative effects of biological and targeted synthetic DMARDs on incident chronic kidney disease in patients with rheumatoid arthritis - Nishimura, Nozomi; Onishi, Akira; Yamamoto, Wataru; Nagai, Koji; Shiba, Hideyuki; Okita, Yasutaka; Son, Yonsu; Amuro, Hideki; Okano, Takaichi; Ueda, Yo; Hara, Ryota; Katayama, Masaki; et al. (Rheumatology, 2025)
Objectives: The impact of individual biological/targeted synthetic DMARD (b/tsDMARD) on kidney function in patients with RA remains unclear. This study aimed to determine the comparative effects of b/tsDMARDs on chronic kidney disease (CKD) incidence in patients with RA. Methods: This multicentre cohort study included patients with RA who had baseline estimated glomerular filtration rate (eGFR) of ≥60 ml/min/1.73 m2 and started a TNF inhibitor (TNFi), cytotoxic T-lymphocyte-associated antigen-4-Ig (CTLA4-Ig), interleukin-6 receptor inhibitor, or Janus kinase inhibitor (JAKi) in Japan. Multiple propensity score-based inverse probability weighting (IPW) was used to adjust confounders. The incidence of CKD was compared among b/tsDMARDs using IPW mixed-effect Cox proportional hazards models and linear mixed-effect models with IPW-examined trajectories of eGFR. Results: Among 2187 patients with 3068 treatment courses and up to 11 years of follow-up, CKD occurred in 275 cases. Compared with the CTLA4-Ig group, the TNFi group had a significantly lower CKD incidence [hazard ratio (HR) 0.67, 95% CI 0.46-0.97, P = 0.04], whereas the JAKi group had a significantly higher incidence (HR 2.16, 95% CI 1.23-3.79, P = 0.01). The trajectory of eGFR was significantly greater in the JAKi group than in the CTLA4-Ig group (CTLA4-Ig: -1.28 ml/min/1.73 m2/year, JAKi: -2.29 ml/min/1.73 m2/year, P < 0.001). Conclusions: TNFi use was associated with reduced CKD incidence, whereas JAKi showed a less protective association for kidney function in patients with RA.
CRIS-Team Scopus Importer:2025-05-16
Keywords: biological DMARD; chronic kidney disease; RA; targeted synthetic DMARD